2002
DOI: 10.1093/jnci/94.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Activity, Bone Matrix Turnover, and Tumor Cell Proliferation in Prostate Cancer Bone Metastasis

Abstract: MMP activity appears to play an important role in bone matrix turnover when prostate cancer cells are present in bone. Bone matrix turnover and metastatic tumor growth appear to be involved in a mutually supportive cycle that is disrupted by MMP inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
156
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(169 citation statements)
references
References 40 publications
12
156
1
Order By: Relevance
“…MMPs are increased in most cancers, including breast and prostate (Upadhyay et al 1999;Bachmeier et al 2001;Nemeth et al 2002), and high levels of MMPs have been associated with poor prognosis (John and Tuszynski 2001;Nakopoulou et al 2002Nakopoulou et al , 2003Ranuncolo et al 2003). In an animal model of prostate cancer osteolytic bone metastasis, MMP-7-deficient mice had less osteolysis due to defective RANKL processing and reduced osteoclast activation (Lynch et al 2005).…”
Section: Mmps In Bone Cancer and Bone Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs are increased in most cancers, including breast and prostate (Upadhyay et al 1999;Bachmeier et al 2001;Nemeth et al 2002), and high levels of MMPs have been associated with poor prognosis (John and Tuszynski 2001;Nakopoulou et al 2002Nakopoulou et al , 2003Ranuncolo et al 2003). In an animal model of prostate cancer osteolytic bone metastasis, MMP-7-deficient mice had less osteolysis due to defective RANKL processing and reduced osteoclast activation (Lynch et al 2005).…”
Section: Mmps In Bone Cancer and Bone Metastasesmentioning
confidence: 99%
“…Several MMPs expressed in bone function in endochondral ossification during embryonic development and in modeling and remodeling of bone postnatally and later in life (Krane and Inada 2008). In support of the latter, mice homozygous for a targeted mutation in Col1a1 that are resistant to collagenase cleavage of type I collagen are resistant to PTH-induced osteoclastic bone resorption (Zhao et al 2000).MMPs are increased in most cancers, including breast and prostate (Upadhyay et al 1999;Bachmeier et al 2001;Nemeth et al 2002), and high levels of MMPs have been associated with poor prognosis (John and Tuszynski 2001;Nakopoulou et al 2002Nakopoulou et al , 2003Ranuncolo et al 2003). In an animal model of prostate cancer osteolytic bone metastasis, MMP-7-deficient mice had less osteolysis due to defective RANKL processing and reduced osteoclast activation (Lynch et al 2005).…”
mentioning
confidence: 99%
“…MMP-9 and MMP-2 have been shown to be capable of cleaving latent TGF-β and activating it [67]. In support of the idea that TGF-β activated by MMPs is key to continuation of the vicious cycle is the finding that MMP inhibition disrupts bone matrix turnover and tumor growth [57]. The release of sequestered TGF-â with subsequent activation thus represents a potentially vital mechanism for enhanced tumor growth.…”
Section: Microenvironment Of Bone Metastasesmentioning
confidence: 99%
“…Gelatinases (MMP-2 and -9) have been found to be associated with prostate cancer metastasis. For example, Nemeth et al 31 have shown higher expression of gelatinases by prostate cancer cells when growing in bone; interestingly, CXCL12 is largely expressed by bone marrow. 32 High MMP-2 and -9 levels in plasma also correlate with prostate cancer metastasis.…”
Section: Cxcr4-mediated Pca Migration and Invasionmentioning
confidence: 99%